2003
DOI: 10.1103/physreve.68.036401
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of multimode weakly nonlinear Rayleigh-Taylor instability in the presence of surface tension

Abstract: A weakly nonlinear model is proposed for the Rayleigh-Taylor instability in the presence of surface tension. The dynamics of a multimode perturbation of the interface between two incompressible, inviscid, irrotational, and immiscible fluids is analyzed. The quadratic and cubic nonlinear effects are taken into account. They include the nonlinear corrections to the exponential growths of the fundamental modulations. The role of the initial modulation spectrum is discussed. A saturation criterion in terms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In most experiments and models, disturbance with only one wave mode has been observed at the boundary [6][7][8][9]. Recently, a model with nonlinear surface tension was calculated whose disturbance has several wave modes [10]. In our experiments of RT instability, however, a fractal pattern without the characteristic length appears at the surface, as shown in Figs.…”
mentioning
confidence: 66%
“…In most experiments and models, disturbance with only one wave mode has been observed at the boundary [6][7][8][9]. Recently, a model with nonlinear surface tension was calculated whose disturbance has several wave modes [10]. In our experiments of RT instability, however, a fractal pattern without the characteristic length appears at the surface, as shown in Figs.…”
mentioning
confidence: 66%
“…We mention that, in the classical Rayleigh-Taylor (RT) experiments [8,12], the phenomenon of that the instability growth is limited by surface tension during the linear stage, where the growth is exponential in time, has been shown. Obviously, the convergence behavior (2.2) mathematically verifies the phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…In classical Rayleigh-Taylor (RT) experiments [8,10], it has been shown that the phenomenon of that surface tension during the linear stage can restrain the instability growth, and the growth is exponential in time. Obviously, this phenomenon can be verified mathematically by the convergence behavior (3.2).…”
Section: Resultsmentioning
confidence: 99%